PEMBELAJARAN MATEMATIKA MENGGUNAKAN THINK TALK WRITE DITINJAU DARI KECERDASAN LOGIKA MATEMATIKA - Suningsih, Ari (JURNAL E-DUMATH, 2016)
This study aims to improve mathematics achievement of the students at MTsGUPPI Kresnomulyo in the academic year 2014-2015 by applying cooperativelearning model, Think Talk Write and direct learning model in terms ofmathematical logic intelligence in high, medium and low categories. This studyincludes quasi experimental with one dependent variable and two independentvariables. The dependent variable is mathematics achievement, and theindependent variable is TTW learning model as the experimental class and directlearning model as the control class. The data analysis was tested by using two-way analysis variance with the measurement 2 x 3. The findings in this study are:(1) the result of cooperative learning TTW type provides the mathematicslearning achievementis better than direct learning; (2) high intelligence ofmathematical logic provides mathematics learning achievement is better thanmedium or low mathematical logic intelligence; and (3) medium mathematicallogic intelligenceis better than low mathematical logic intelligence. It isapplicable in every learning model in higher mathematics logic intelligence isbetter than medium or low mathematical logic intelligence.Keywords: think talk write, cooperative learning model, mathematical logicintelligence